The Relationship Between Leadership Styles in The Pentecostal Assembilies of God,Uganda: A Case Study of Churches in Nothern Region - Omara, Joel G (Pan Africa Christian University, 2015)
For any growing organization effective leadership is inevitably essential. Leaders use diverse leadership styles as a tool in order to attain goals and objectives of their organization. Leadership styles become an integral part of a leader consequently creating either positive or negative dynamics within the organization depending on the manner they are used. The purpose of this study is to investigate the relationship between leadership styles and conflicts in Pentecostal Assemblies of God in Uganda. Different leadership styles and causes of church conflicts were surveyed and the findings helped to relate leadership styles to conflicts. The research design was qualitative and quantitative ministered through self administered questionnaire with structured and unstructured questions. The research was limited to five sampled Assemblies in Lira Pastorate and the target population was eight hundred leaders who occupy pastoral positions in PAG churches. The help of a statistician was sought to analyze the data with the aid of SPSS software. The study shows a relationship between leadership styles and conflicts in PAG church. It also revealed that the most dominant leadership style in the churches in Northern Uganda especially in Lira Pastorate is dictatorial/autocratic style and it exposed other causes of conflicts as well. In the light of these discoveries PAG church should consider proper procedure of recruitment of people into leadership and equip them with leadership skills centered on the changeless character of Christ. PAG should also intentionally empower leaders with conflict management skills since conflicts are unavoidable. The key words in the research were leadership styles, conflicts and relationship.
Keywords: Types of Leadership Styles,Autocratic Leadership Style,Delegating Leadership Style